Dendritic cells and the intestinal bacterial flora: a role for localized mucosal immune responses. - Uhlig, H; Powrie, F (2003)
Mammals coexist in an overall symbiotic relationship with a complex array of commensal bacterial flora that colonizes the gastrointestinal tract. These intestinal bacteria interface with cells of the mucosal immune system, including DCs. Here we discuss mechanisms of interaction between intestinal bacteria and DCs and the role of localized gastrointestinal immune responses.